Fluid-Structure Interaction Simulations of Repaired Type A Aortic Dissection: a Comprehensive Comparison With Rigid Wall Models - Zhu, Yu; Mirsadraee, Saeed; Rosendahl, Ulrich; Pepper, John; Xu, Xiao Yun (Frontiers in Physiology, 2022)
This study aimed to evaluate the effect of aortic wall compliance on intraluminal hemodynamics within surgically repaired type A aortic dissection (TAAD). Fully coupled two-way fluid-structure interaction (FSI) simulations were performed on two patient-specific post-surgery TAAD models reconstructed from computed tomography angiography images. Our FSI model incorporated prestress and different material properties for the aorta and graft. Computational results, including velocity, wall shear stress (WSS) and pressure difference between the true and false lumen, were compared between the FSI and rigid wall simulations. It was found that the FSI model predicted lower blood velocities and WSS along the dissected aorta. In particular, the area exposed to low time-averaged WSS (≤0.2 Pa) was increased from 21 cm2 (rigid) to 38 cm2 (FSI) in patient 1 and from 35 cm2 (rigid) to 144 cm2 (FSI) in patient 2. FSI models also produced more disturbed flow where much larger regions presented with higher turbulence intensity as compared to the rigid wall models. The effect of wall compliance on pressure difference between the true and false lumen was insignificant, with the maximum difference between FSI and rigid models being less than 0.25 mmHg for the two patient-specific models. Comparisons of simulation results for models with different Young’s moduli revealed that a more compliant wall resulted in further reduction in velocity and WSS magnitudes because of increased displacements. This study demonstrated the importance of FSI simulation for accurate prediction of low WSS regions in surgically repaired TAAD, but a rigid wall computational fluid dynamics simulation would be sufficient for prediction of luminal pressure difference.